2023
DOI: 10.3390/nu15020450
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Essential Oil Blend on Growth Performance, Intestinal Health, and Microbiota in Early-Weaned Piglets

Abstract: Essential oils (EO) are promising feed additives for their antibacterial, antioxidant, and immune-enhancing abilities with low toxicity. Carvacrol, thymol, and cinnamaldehyde are commonly used to synthesize EO. However, few studies focus on combining these three EO in early-weaned piglets. In the present study, 24 piglets weaned at 21 d of age were randomly divided into 2 groups (6 replicate pens per group, 2 piglets per pen). The piglets were fed a basal diet (the control group) and a basal diet supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…However, no significant difference or trend was observed in the later stage of this animal trial across all groups regarding the content of short-chain fatty acids. In previous studies, dietary supplementation with 400 mg/kg essential oil mixtures (carvacrol, thymol and cinnamaldehyde) had no significant effects on volatile fatty acid concentrations in colon of piglets, and analysis of microbial α-diversity and β-diversity showed little difference [49]. In this study, although short-chain fatty acids concentrations were not affected, microbial diversity was changed.…”
Section: Effects Of Essential Oil Mixture Supplementation On Short-ch...contrasting
confidence: 48%
“…However, no significant difference or trend was observed in the later stage of this animal trial across all groups regarding the content of short-chain fatty acids. In previous studies, dietary supplementation with 400 mg/kg essential oil mixtures (carvacrol, thymol and cinnamaldehyde) had no significant effects on volatile fatty acid concentrations in colon of piglets, and analysis of microbial α-diversity and β-diversity showed little difference [49]. In this study, although short-chain fatty acids concentrations were not affected, microbial diversity was changed.…”
Section: Effects Of Essential Oil Mixture Supplementation On Short-ch...contrasting
confidence: 48%
“… Kong et al (2023) reported that GML had a protective effect on intestinal morphology by improving the VH of the small intestine in challenged chicken embryos. Shao et al (2023) reported that the essential oil containing 13.8% cinnamaldehyde can significantly increase the VH and the VH/CD in the ileum of piglets, thus promoting the development of intestinal epithelium. In the current study, it was observed that the combination of GML and cinnamaldehyde in the diet of laying hens significantly increased the VH, the VH/CD of small intestine, and the duodenal villus area, decreased the duodenal and jejunal CD, and thus improved the digestibility and absorption rate of feed.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study by Kroismayr and co-workers [58,59] showed a tendency for essential oils to reduce villus length in the jejunum and ileum, whereas other previous reports showed no change in pigs [81]. The effects of dietary supplementation with a mixture of EOs, including thyme oil, were investigated in weaned piglets [82]. The study reported that piglets receiving the EO blend had improved growth performance.…”
Section: Effects O F Eos On the Diet O F Animals On Performance And N...mentioning
confidence: 99%
“…The study reported that piglets receiving the EO blend had improved growth performance. This may be related to the beneficial effects of thyme EO on the gut environment, nutrient absorption and general health [82].…”
Section: Effects O F Eos On the Diet O F Animals On Performance And N...mentioning
confidence: 99%